Patellar instability following experimental medial patellar desmotomy in horses - Baccarin, R. Y. A.; Martins, E. A. N.; Hagen, S. C. F.; Silva, L. C. L. C. (Veterinary and Comparative Orthopaedics and Traumatology, 2009)
A controlled study was designed in order to evaluate the effects of medial patellar desmotomy (MPD), combined with exercise restriction, on clinically and radio-graphically normal femoropatellar joints, and to identify the patellar instability by radiographic examination. MPD was performed on the right hind limb and the horses were rested for 120 days. Both hind limbs were radiographed before surgery and at 15, 30, 60, 90, and 120 days after MPD, obtaining lateromedial, flexed lateromedial, caudocranial and cranioproximal-craniodistal (skyline) views. The femorotibial and femoropatellar angles were assessed on the lateromedial views, and the distance between the medial and lateral cortex of the femur, and the distance between the medial cortex of the femur and the lateral border of the patella were evaluated in the caudocranial views. An increase in the angle between the proximal articular surface of the patella and the cranial distal surface of the femur along with enthesophyte formation and lateral deviation of the patella were found on the radio-graphs of the right stifles after MPD. Therefore, MPD leads to patellar instability, which can be demonstrated by the radiographic changes. The 120 days rest did not prevent the lesions caused by postsurgical patellar instability.
Keywords: Medial patellar desmotomy; upward fixation of patella; stifle; radiographic exam; horse